2008
DOI: 10.1093/geront/48.6.828
|View full text |Cite
|
Sign up to set email alerts
|

Healthy IDEAS: Implementation of a Depression Program Through Community-Based Case Management

Abstract: Successful adoption and sustainability of HIDEAS are more likely when essential elements of the Core Implementation Component framework are addressed to bring about behavioral changes at all treatment-implementation levels-clients, practitioners, and organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…However, it is unclear whether peer educators or community health workers could provide BTB as knowledge and comfort with discussing mental health concerns, using motivational interviewing and behavioral activation techniques may require more training. An evaluation of a depression treatment with similar components as BTB implemented by care managers suggested that this group may be reluctant to use behavioral activation due to their lack of mental health training (Casado et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether peer educators or community health workers could provide BTB as knowledge and comfort with discussing mental health concerns, using motivational interviewing and behavioral activation techniques may require more training. An evaluation of a depression treatment with similar components as BTB implemented by care managers suggested that this group may be reluctant to use behavioral activation due to their lack of mental health training (Casado et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of these efforts is for psychologists to understand the strengths and limitations of local community resources relative to their domains of practice, or the risk factors affecting the older adult group of concern. For example, if attempting to reduce isolation as a risk factor for depression, it might be pertinent to consider the availability of organized opportunities for older adult socialization and whether to increase these (Casado et al, 2012). Similarly, relative to fostering older adults' general sense of well-being, it might be useful to advocate for more health promotion activities designed to facilitate their participation in exercise, good nutrition, and healthy lifestyles (www.cdc.govaging).…”
Section: Intervention Consultation and Other Service Provisionmentioning
confidence: 99%
“…On a promising note, even though the model had limited sustainability, the sustained partnership provided the foundation for a larger state initiative around geriatric mental health care through a Substance Abuse and Mental Health Services Administration transformation grant. This initiative pursued an alternative adaptation of collaborative care for community-based social services for older adults that has demonstrated promise for both effectiveness and sustainability—Healthy IDEAS (Casado et al, 2008). Healthy IDEAS used a community-based coalition to adapt collaborative care and did not attempt to place a specialized depression care manager in a single provider system.…”
Section: Discussionmentioning
confidence: 99%